2014
DOI: 10.1016/j.ygeno.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Application of a low cost array-based technique — TAB-Array — for quantifying and mapping both 5mC and 5hmC at single base resolution in human pluripotent stem cells

Abstract: 5-hydroxymethylcytosine (5hmC), an oxidized derivative of 5-methylcytosine (5mC), has been implicated as an important epigenetic regulator of mammalian development. Current procedures use DNA sequencing methods to discriminate 5hmC from 5mC, limiting their accessibility to the scientific community. Here we report a method that combines TET-assisted bisulfite conversion with Illumina 450 K DNA methylation arrays for a low-cost high-throughput approach that distinguishes 5hmC and 5mC signals at base resolution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 34 publications
1
38
1
Order By: Relevance
“…Highly active TET proteins are required for the efficient conversion of 5mC to 5caC (more than 96 %), or else the incomplete conversion of 5mC might lead to false identification as 5hmC sites [ 81 ]. Both oxidative bisulfite conversion and TET-assisted bisulfite conversion are compatible with microarray and sequencing platforms to generate the 5hmC methylation profile for a whole genome or targeted regions [ 82 ]. The relatively low levels of 5hmC and the subtraction step demand an increase in the sequencing coverage and the number of replicates.…”
Section: Experimental Techniques For Dna Methylation Profilingmentioning
confidence: 99%
“…Highly active TET proteins are required for the efficient conversion of 5mC to 5caC (more than 96 %), or else the incomplete conversion of 5mC might lead to false identification as 5hmC sites [ 81 ]. Both oxidative bisulfite conversion and TET-assisted bisulfite conversion are compatible with microarray and sequencing platforms to generate the 5hmC methylation profile for a whole genome or targeted regions [ 82 ]. The relatively low levels of 5hmC and the subtraction step demand an increase in the sequencing coverage and the number of replicates.…”
Section: Experimental Techniques For Dna Methylation Profilingmentioning
confidence: 99%
“…An emerging issue relates to the inability of sodium bisulfite conversion, which is the commonly used method for determination of 5-mC at single-base resolution, to distinguish 5-mC from its oxidative derivative 5-hydroxymethylcytosine (5-hmC) [ 131 ]. It has been reported that 5-hmC is enriched in intergenic regions, including LINE-1 elements and gene body regions [ 132 - 134 ]. In studies evaluating the association of DNA methylation and environmental chemicals using bisulfite conversion based methods for DNA methylation assessment, residual measurement error by 5-hmC content is, thus, possible.…”
Section: Reviewmentioning
confidence: 99%
“…Different from 5-mC, 5-hmC has an abundance within the genome 10-100-fold lower than that of 5-mC, and the abundances of 5-foC and 5-caC are about 40-1000-fold higher than that of 5-hmC [70][71][72]. These C modifications are a hot spot, and the analytical methods have been developed significantly, and mainly involve the application of LC, CE, bioaffinity or chemical derivatization, such as recombinant β-glucosyltransferase analysis [73], selective chemical labeling [74], combined glycosylation restriction analysis [75], and TAB-array [76].…”
Section: Discussionmentioning
confidence: 99%